Correction: TGFβ-activation by dendritic cells drives Th17 induction and intestinal contractility and augments the expulsion of the parasite Trichinella spiralis in mice. - Nicola Steel; Aduragbemi A Faniyi; Sayema Rahman; Stefanie Swietlik; Beata I Czajkowska; Bethany T Chan; Alexander Hardgrave; Anthony Steel; Tim D Sparwasser; Mushref B Assas; Richard K Grencis; Mark A Travis; et al. (PLoS Pathogens)
[This corrects the article DOI: 10.1371/journal.ppat.1007657.].